1998
DOI: 10.1016/s0169-7722(98)00054-0
|View full text |Cite
|
Sign up to set email alerts
|

Contamination in Ontario farmstead domestic wells and its association with agriculture:

Abstract: Groundwater provides about 30% of water requirements in Ontario, but farm families depend almost entirely on private wells. Major potential contaminants on farms are nitrate (NO ), pathogenic micro-organisms, pesticides and petroleum derivatives. A survey of farm 3 drinking water wells was conducted throughout the Province of Ontario, Canada, in 1991 and 1992 and tested for these contaminants. Main objectives of the survey were to determine the quality and safety of drinking water for farm families, and determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
95
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(111 citation statements)
references
References 23 publications
12
95
1
3
Order By: Relevance
“…As a result of the mentioned study, nitrate levels in 15.7% of investigated wells had exceeded the critical limit of 10 mg/L [30]. In another study that investigated nitrate in Ontario, Canada, 14% of farmstead domestic wells contained nitrate above the 10 mg/L limit [31]. In the present study, nitrate contents in 23% of investigated stations including Tevfikiye, Karaağaç, and İbriktepe, which have formed a separate cluster (C6) in Cluster Analysis (CA), and Esetçe stations were recorded as quite close to the EPA maximum contaminant level (MCL) of 10 mg/L (8.840 mg/L, 9.160 mg/L, 8.410 mg/L and 9.730 mg/L respectively), and also nitrate concentrations recorded in Pazardere station, which has formed a separate cluster (C3) in CA, has exceeded the MCL limit two times (19.3 …”
Section: Discussionmentioning
confidence: 74%
“…As a result of the mentioned study, nitrate levels in 15.7% of investigated wells had exceeded the critical limit of 10 mg/L [30]. In another study that investigated nitrate in Ontario, Canada, 14% of farmstead domestic wells contained nitrate above the 10 mg/L limit [31]. In the present study, nitrate contents in 23% of investigated stations including Tevfikiye, Karaağaç, and İbriktepe, which have formed a separate cluster (C6) in Cluster Analysis (CA), and Esetçe stations were recorded as quite close to the EPA maximum contaminant level (MCL) of 10 mg/L (8.840 mg/L, 9.160 mg/L, 8.410 mg/L and 9.730 mg/L respectively), and also nitrate concentrations recorded in Pazardere station, which has formed a separate cluster (C3) in CA, has exceeded the MCL limit two times (19.3 …”
Section: Discussionmentioning
confidence: 74%
“…In Ontario, private wells where manure is commonly applied on farms are frequently contaminated with bacteria. Feces contaminated effluents from animal farms infiltrate wells [70]. In addition, waste from septic tanks and manure storage sites can seep or spill into surrounding watersheds and ground water sources [71].…”
Section: Infiltration Of Antibiotics and Antibiotic Resistance Into Tmentioning
confidence: 99%
“…The authors also showed that when the shallow groundwater leaves the agricultural areas, the nitrate concentration quickly decreases mainly due to denitrification. Goss et al (1998) studied the pollution of the shallow groundwater in some farms of Ontario, Canada. The authors also examined the factors influencing the degree of contamination and proved, based on the examinations of 1292 wells, that the degree of nitrate pollution principally depends on the depth of the shallow groundwater.…”
Section: Wwwintechopencommentioning
confidence: 99%